Social representations of the reproductive health bill - Calleja, Mendiola T. (Philippine journal of psychology, 2009)
"To investigate the social representations of the Reproductive Health (RH) Bill, this research examined newspaper articles that captured the intense public debate on the legislation of the bill. Content analysis and discriminant procedures showed that the discourse on the RH Bill primarily wove a contested story about contraception. The debate on sex education and poverty was found to be secondary."